Daya Saing Ekspor Karet Alam Manufaktur Indonesia di Pasar Internasional (Jurnal Agribisnis Indonesia, 2024)
This research is about the competitiveness of manufactured natural rubber which includes TSNR (Technically Specified Natural Rubber) rubber, RSS (Rubber Smooked Sheets) rubber and Rubber Gloves in the 2000-2020 time period. The analytical tools used are Revealed Comparative Advantage (RCA) to determine comparative competitiveness, Market Share Index (MSI) to determine how much influence Indonesia's manufactured natural rubber exports have to destination countries and the world. This study also use Spearman Rank Correlation to determine the relationship between the competitiveness of Indonesian manufacturing natural rubber with competing countries. The research results show that Indonesian manufactured natural rubber has strong competitiveness with RCA>1. However, Indonesia is only able to dominate TSNR rubber compared to Thailand and Malaysia in the largest importer countries of rubber manufacturing in the markets of the United States, Japan and China. RSS Rubber is only able to rank second below Thailand in dominating the international market and exports to destination countries. Meanwhile, Indonesian Rubber Gloves are unable to be competitive when compared to Malaysia as the largest exporter and Thailand as well as to export destination countries. Indonesia's TSNR competitiveness has a medium and unidirectional relationship with Thailand, while it has a strong and unidirectional relationship with Malaysia. The competitiveness of the Indonesian RSS with Thailand and Malaysia has a weak and unidirectional relationship. Meanwhile, the competitiveness of Indonesian Rubber Gloves has a moderate and unidirectional relationship with Thailand, while it has a weak and unidirectional relationship with Malaysia.